2006
DOI: 10.1002/app.24506
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in processability of metallocene polyethylene by ultrasound and binary processing aid

Abstract: The effect of ultrasonic vibration and binary processing aid in improving the processability of metallocene linear low-density polyethylene (mLLDPE) was investigated. During extrusion, ultrasonic vibration clearly reduced the die pressure and apparent viscosity of mLLDPE but had only a slight effect on its melt fracture. The effect of diatomite/PEG binary processing aid (BPA) was excellent in reducing the viscosity and eliminating the sharkskin fracture of mLLDPE. The effect of ultrasonic vibration and binary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Ultrasonically aided extrusion also led to an improvement of the elongation at break of LDPE/LLDPE blends 29. An addition of the diatomite/polyethylene glycol mixture to LLDPE led to an increase of the critical shear rate for the onset of sharkskin fracture and, in the presence of ultrasonic treatment, an improvement of the processibility of the LLDPE mixture was reported 30…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Ultrasonically aided extrusion also led to an improvement of the elongation at break of LDPE/LLDPE blends 29. An addition of the diatomite/polyethylene glycol mixture to LLDPE led to an increase of the critical shear rate for the onset of sharkskin fracture and, in the presence of ultrasonic treatment, an improvement of the processibility of the LLDPE mixture was reported 30…”
Section: Introductionmentioning
confidence: 87%
“…A few studies on the effect of ultrasound on pure LLDPE were reported 27–30. In particular, they showed that an ultrasonically aided single screw extrusion improved processing of LLDPE by reducing the die pressure and melt viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…Li and coworkers [76] described the use of PEG as a processing aid for extrusion of UHMW PE/PP blend. Li and coworkers [77,78] also report a suppression of sharkskin melt fracture for additives of a binary blend of PEG and diatomaceous earth in amounts from 0.5 to 3 wt%. According to the authors, the blend works synergistically and PEG alone does not suppress sharkskin melt fracture.…”
Section: Peg In Lubricants and Ppamentioning
confidence: 96%
“…[2][3][4] Literature on eliminating these flow instabilities have pointed out that mPE could be prepared by the improvement of synthesis techniques, using composite catalyst to produce bimodal or broad molecular weight distribution of mPE, [5][6][7] blending with similar chain structure polymers such as HDPE, LDPE, LLDPE, long chain branched PE, and UHMWPE, [8][9][10][11][12] filling with flow modifier [13][14][15] or amending the processing equipment of polyolefins. 16,17 Mechanochemical modification is an easy and efficient method for improving rheological properties of mPE. When an external force is exerted on the covalent bonds of polymer chains, they will deform and even to breakdown if the external energy is beyond the covalent bond energy, which will produce macroradicals.…”
Section: Introductionmentioning
confidence: 99%